Pengaruh Pengetahuan Perpajakan, Sanksi Pajak, Kualitas Pelayanan Fiskus Terhadap Kepatuhan Wajib Pajak Orang Pribadi Dengan Kesadaran Pajak Sebagai Variabel Moderasi - Nafatika Indriyani Simbolon; Linda Wahyu Marpaung; Albert Herlambang; Johnny Chandra (Politeknik Ganesha Medan, 2026)
This study aims to analyze the effect of tax knowledge, tax sanctions, and the quality of tax officer services on individual taxpayer compliance, with tax awareness as a moderating variable. The research was conducted at KPP Pratama Medan Timur. The population consisted of 130,468 individual taxpayers, with a sample of 400 respondents determined using purposive sampling and the Slovin formula. Data were collected through questionnaires using a 1–5 Likert scale. The analytical methods employed included descriptive statistics, classical assumption tests (normality, multicollinearity, linearity, heteroscedasticity), multiple regression analysis, Moderated Regression Analysis (MRA), as well as the coefficient of determination (R²), F-test, and t-test using SPSS version 26. The results showed that: (1) tax knowledge has a positive and significant effect on individual taxpayer compliance; (2) tax sanctions have a positive and significant effect; (3) the quality of tax officer services has a positive and significant effect; (4) tax awareness has a positive and significant effect; (5) tax awareness strengthens the effect of tax knowledge on compliance; (6) tax awareness does not moderate the effect of tax sanctions on compliance; (7) tax awareness strengthens the effect of the quality of tax officer services on compliance. The coefficient of determination (R²) value of 0.612 indicates that 61.2% of the variation in taxpayer compliance is explained by the independent and moderating variables, while the remaining 38.8% is explained by other variables outside the research model. This study concludes that tax knowledge, tax sanctions, quality of tax officer services, and tax awareness simultaneously and partially affect individual taxpayer compliance at KPP Pratama Medan Timur. Tax awareness acts as a moderating variable that strengthens the relationship between tax knowledge and compliance, as well as between the quality of tax officer services and compliance, but does not strengthen the relationship between tax sanctions and compliance.